Contemporary Jewish Genealogy: Assuming the Role of Former Landsmanshafts - Kamila Klauzinska (Genealogy, 2024)
To understand the changing trends in Jewish Genealogy over the past 40 years, the author has interviewed more than one hundred genealogists around the world. All of them are connected to the two most important genealogy organisations, JewishGen and JRI-Poland. They range from hobbyists researching their own families to professionals researching specific prewar Polish shtetls and those serving the entire genealogical community. Based on their responses to 26 questions, the author has identified two important features of contemporary Jewish genealogy: its democratisation and institutionalisation. The democratisation of genealogical research has contributed to a great expansion of the field. The focus of interest is no longer limited to only rabbinical families but is also concerned with the common man. Thus, genealogists today speak not only on behalf of sheyne yidn and otherwise distinguished families but also on behalf of the millions of murdered „ordinary” Jews who once lived in Poland. The institutionalisation of genealogy refers to the degree to which genealogical research organisations like JewishGen or JRI-Poland now provide some of the same functions provided years ago by the landsmanshaft institutions. Today, descendants of a particular shtetl often discover and connect to each other through genealogical researchers and these genealogical organisations. How these Jewish genealogical practices can be/are used to strengthen the landsmanshaft-like function will be examined.